Tracking the rainbow: recent trends in LGBT reference and collection development. Issue 7 (9th September 2014) - Ridinger, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to assess the state of reference publishing between 2003 and 2013 in print, online databases (free access and fee-based) and Internet sites for the field of lesbian, gay, bisexual and transgender (LGBT) studies. Background data on trends in non-reference monographic publishing and the growth of topical websites covering LGBT-related subjects are provided. Design/methodology/approach – The WorldCat bibliographical database was scanned for titles published during the decade 2003-2013 to ascertain trends in subject monographs within LGBT studies. The status of the pool of LGBT websites reviewed by the author in 2005 for Choice was checked to evaluate the stability of this expanding format of LGBT information. Those reference works and online resources identified were annotated and placed in the context of general LGBT reference publishing. Findings – Results of the study showed that the genres of encyclopaedias and handbooks continued to be produced for LGBT studies during the first decade of the twenty-first century. The creation of a database of full-text primary materials (ranging from newspapers and academic periodicals to research monographs) marks the recognition by the research community of the value of this body of formerly marginalized literature. The stability of the group of subject websites produced on LGBT topics delineated by the author in 2005 indicates that these resources can be effectively used in the reference process. Originality/value – The data in this article will assist librarians engaged in collection development and reference work by providing a contemporary analysis and bibliographic overview of the sources and types of reference tools in a new interdisciplinary field.